"They've Put Nothing in the Pot!": Brexit and the Key Psychological Motivations Behind Voting 'Remain' and 'Leave'. Issue 5 (17th March 2020) - Macdougall, Alex I.; Feddes, Allard R.; Doosje, Bertjan
Abstract : In June 2016, the United Kingdom voted to leave the European Union. Voting followed a general trend: disadvantaged areas of the United Kingdom tended to vote "leave, " and more affluent areas tended to vote "remain." This project investigates the psychological variables underlying this overall trend by distinguishing four psychological motivations: the need for justice, threat reduction needs, need to belong, and the need for control. Participants were recruited from different areas across Greater Manchester ( N  = 158). A survey assessed voting preference, socioeconomic status, collective relative deprivation (CRD), perceptions of threat from immigration, European and British identification, sense of control in life, and relative gratification. Discriminant function analysis showed that leave voting was characterized by greater realistic threat, symbolic threat, CRD, and British identification. Remain voting was characterized by strong European identification. Findings highlight that a need for justice, threat‐reduction needs, and identity needs were key predictors of voting behavior.